Dialectical Materialism and Social Change: A Marxist Perspective on Societal Transformation - Budhathoki, Drona (International Research Journal of MMC, 2026)
Historical Dialectical Materialism is a Marxist framework that explains social change through the interaction of material conditions and human activity. It posits that history progresses via contradictions within economic and social structures, leading to conflict and transformation. Society’s development is driven by the tension between forces of production and relations of production, ultimately shaping political, cultural, and social institutions. This perspective emphasizes that change is not random but rooted in material realities, highlighting the dynamic, interconnected nature of history and society. The Chief objective is to examine how dialectical materialism explains the mechanisms of social change from a Marxist perspective. This study adopts an explanatory research design to investigate the relevance of dialectical materialism in social change. It primarily relies on qualitative data, collected through a review of selected books, academic articles, and critical texts. The research focuses on both global and Nepali contexts, synthesizing insights to analyze how contradictions within economic and social structures drive societal transformation. This study demonstrates that dialectical materialism, as conceptualized by Marx and Engels, provides a comprehensive framework for analyzing social change through the interplay of material forces and production relations. Class conflicts and contradictions within economic structures drive transformation. Technological advancement, inequality, and neoliberal policies create new tensions, confirming their relevance in transitional societies like Nepal. This study is significant as it applies dialectical materialism to analyze how material conditions and class relations drive social change. This study helps fill the gap in research within both the Nepalese and global contexts. It will be valuable for those seeking to understand social dynamics and for providing insights to guide socio-economic transformation.